2021
DOI: 10.1101/2021.01.11.21249549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship between Democracy embracement and COVID-19 reported casualties worldwide

Abstract: BackgroundThe COVID-19 toll of cases and deaths followed an uneven pattern across the world. The literature has partly explained the observed discrepancy between the different countries by country-specific and systemic patterns worldwide. In this study, we propose an additional explanation that the magnitude of COVID-19 toll reported to the WHO could be influenced by the level of free speech and Democracy in the reporting countries.MethodsWe constructed a longitudinal dataset including the daily COVID-19 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The findings present an opportunity for the U.S. to improve its health care system, building on the ongoing efforts to ensure accuracy of its COVID-19 counting; an advantage not available in many other countries. 20 The results show that COVID-19 epidemic spread at a significantly slower rate in the expansion states than the nonexpansion states. It took almost two additional days for COVID-19 case numbers to double in Medicaid expansion states than in the nonexpansion states.…”
Section: Discussionmentioning
confidence: 91%
“…The findings present an opportunity for the U.S. to improve its health care system, building on the ongoing efforts to ensure accuracy of its COVID-19 counting; an advantage not available in many other countries. 20 The results show that COVID-19 epidemic spread at a significantly slower rate in the expansion states than the nonexpansion states. It took almost two additional days for COVID-19 case numbers to double in Medicaid expansion states than in the nonexpansion states.…”
Section: Discussionmentioning
confidence: 91%
“…Only Mazzucchelli et al (2020) have systematically examined the impact of specific democratic institutions and practices on COVID-19 deaths, albeit only in Europe. Two other studies investigate the impact of one or two democratic components (Bosancianu et al 2020, Hussein et al 2021. In sum, the existing literature does not provide guidance about regime types' and their components' impact on all epidemics.…”
Section: Existing Workmentioning
confidence: 99%
“…Fewer studies have examined the impact of democracy on COVID-19 deaths (e.g. Bosancianu et al 2020, Cassan and Steenvort 2021, Cepaluni et al 2020, Hussein et al 2021, Mazzucchelli et al 2020, Sorci et al 2020. Earlier studies found a positive association between democracy and COVID-19 deaths; later studies found no association.…”
Section: Existing Workmentioning
confidence: 99%
“…Recently, the degree of freedom of speech and democracy, as measured by the Freedom in the World Index (FWI), has been used to better understand the COVID-19 response of individual governments, particularly in reporting case numbers and death tolls (Hussein et al, 2020). Unlike in the GI and GII, Latin American countries have very different degrees of FWI, with some countries considered "Free" such as Chile, while others considered "Not Free" like Cuba and Venezuela (Santiago et al, 2020).…”
Section: The Reasons Behind Chlorine Dioxide Consumption In Latin Americamentioning
confidence: 99%